Choice of an Infusion Agent for the Prevention of Multiple Organ Dysfunction in Acute Massive Blood Loss (Experimental Study) - A. Yu. Yakovlev; N. V Yemelyanov; I. V. Mukhina; A. V., Dvornikov; L. B. Snopova; G. V. Kalentyev; D. V. Ryabikov; N. V. Mineyeva (Общая реаниматология)
Objective: to perform an experimental study of the effect of sterofundin isotonic on the biochemical parameters characterizing the degree of organ injury after acute massive blood loss (AMBL). Material and methods. Experiments were carried out on 36 male Wistar rats weighing 230—250 g. Hemorrhagic stroke was simulated via AMBL in a volume of 2.5 ml/100 g at a rate of 2 ml/min. An hour after AMBL, there was hypovolemia compensation within 60 minutes in a volume of 200% of the blood loss: by Ringer’s solution in a control group and by sterofundin isotonic in an experimental group. Then blood reinfu-sion was made in a volume of 70% of blood loss. The biochemical parameters of multiple organ dysfunction (glucose, lactate, urea, creatinine, bilirubin, total protein, albumin), enzymemia (aspartate aminotransferase, alanine aminotransferase, creatine phosphokinase, lactate dehydrogenase, amylase), endotoxemia (low- and medium-molecular-weight substances in the plasma and erythrocytes), acid-base condition, electrolytes of venous blood, and animal survival were determined on days 1 and 3 following AMBL. Results. There was a reduction in the time and degree of posthemorrhagic metabolic, biochemical, and electrolyte disorders, enzymemia, and endotoxemia in the experimental animals. Conclusion. The experimental studies suggest that Ringer’s solution is inadequately effective in preventing multiple organ dysfunction due to AMBL. The malate-containing blood substitute sterofundin isotonic that is used during early therapy for AMBL exerts a marked preventive effect on the development of visceral organ injuries when multiple organ dysfunction occurs in the early and late posthemorrhagic period. The experimental findings make it possible to recommend that sterofundin isotonic should be used in intensive care of hypovolemic shock arising from AMBL. Key words: acute massive blood loss, malate, sterofun dinisotonic, lactate, endotoxemia, multiple organ dysfunction.